Earth : the incredible recycling machine - "Bennet Paul" (Hove Wayland, 1993)
"Earth, the Incredible Recycling Machine" by Paul Bennett is a 1993 publication that introduces readers to essential natural cycles involving water, carbon, nitrogen, sulfur, and phosphorus$1 (Belements vital for the growth and reproduction of plants and animals. The book explains how human activities have disrupted these cycles, leading to environmental imbalances. It is illustrated with color photographs and artwork throughout.s